New evidence for the cerebellar involvement in personality traits - Picerni, Eleonora; Petrosini, Laura; Piras, Fabrizio; Laricchiuta, Daniela; Cutuli, Debora; Chiapponi, Chiara; Fagioli, Sabrina; Girardi, Paolo; Caltagirone, Carlo; Spalletta, Gianfranco (Frontiers in Behavioral Neuroscience, 2013)
Following the recognition of its role in sensory-motor coordination and learning, the cerebellum has been involved in cognitive, emotional and even personality domains. This study investigated the relationships between cerebellar macro- and micro-structural variations and temperamental traits measured by Temperament and Character Inventory (TCI). High resolution T1-weighted and Diffusion Tensor Images of 100 healthy subjects aged 18-59 years were acquired by 3 Tesla Magnetic Resonance scanner. In multiple regression analyses, cerebellar Gray Matter (GM) or White Matter (WM) volumes, GM Mean Diffusivity (MD), and WM Fractional Anisotropy (FA) were used as dependent variables, TCI scores as regressors, gender, age, and education years as covariates. Novelty Seeking scores were associated positively with the cerebellar GM volumes and FA, and negatively with MD. No significant association between Harm Avoidance, Reward Dependence or Persistence scores and cerebellar structural measures was found. The present data put toward a cerebellar involvement in the management of novelty.